Population pharmacokinetics of tigecycline in critically ill patients - Luo, Xiangru; Wang, Shiyi; Li, Dong; Wen, Jun; Sun, Na; Fan, Guangjun (Frontiers in Pharmacology, 2023)
Objective: In critically ill patients, the change of pathophysiological status may affect the pharmacokinetic (PK) process of drugs. The purpose of this study was to develop a PK model for tigecycline in critically ill patients, identify the factors influencing the PK and optimiz dosing regimens. Method: The concentration of tigecycline was measured LC-MS/MS. We established population PK model with the nonlinear mixed effect model and optimized the dosing regimens by Monte Carlo simulation. Result: A total of 143 blood samples from 54 patients were adequately described by a one-compartment linear model with first-order elimination. In the covariate screening analysis, the APACHEII score and age as significant covariates. The population-typical values of CL and Vd in the final model were 11.30 ± 3.54L/h and 105.00 ± 4.47L, respectively. The PTA value of the standard dose regimen (100 mg loading dose followed by a 50 mg maintenance dose at q12h) was 40.96% with an MIC of 2 mg/L in patients with HAP, the ideal effect can be achieved by increasing the dosage. No dose adjustment was needed for Klebsiella pneumoniae for AUC0–24/MIC targets of 4.5 and 6.96, and the three dose regimens almost all reached 90%. A target AUC0–24/MIC of ≥17.9 reached 100% in patients with cSSSI in the three tigecycline dose regimens, considering MIC ≤0.25 mg/L. Conclusion: The final model indicated that APACHEII score and age could affect the Cl and Vd of tigecycline, respectively. The standard dose regimen of tigecycline was often not able to obtain satisfactory therapeutic effects for critically ill patients. For patients with HAP and cIAI caused by one of three pathogens, the efficacy rate can be improved by increasing the dose, but for cSSSI infections caused by Acinetobacter baumannii and Klebsiella pneumoniae, it is recommended to change the drug or use a combination of drugs.